2013
DOI: 10.1007/s11434-013-5800-8
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and genotoxicity of multi-walled carbon nanotubes with human ocular cells

Abstract: Cytotoxicity and genotoxicity of plasma-modified multi-walled carbon nanotubes (MWCNTs), including hydroxyl-MWCNTs (MWCNT-OH), carboxyl-MWCNTs (MWCNT-COOH) and pristine MWCNTs, with human ocular cells (e.g. retinal pigment epithelium (RPE) cells) have been studied in this work. The addition of MWCNT-based materials caused few change in cell morphology while the presence of MWCNTs was observed inside the cells using transmission electron microscopy (TEM), suggesting possibility of MWCNTs passing through the cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…MWNT has different toxicity such as inhalation toxicity, genotoxicity and so forth. [67][68][69] Ag nanoparticle is one of the nanostructures used in different parts of life especially as the antimicrobial agent. 33,34 Toxicity of CNTs have been widely investigated by different groups and showed that their toxicity is related to composition, length, diameter and sizes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MWNT has different toxicity such as inhalation toxicity, genotoxicity and so forth. [67][68][69] Ag nanoparticle is one of the nanostructures used in different parts of life especially as the antimicrobial agent. 33,34 Toxicity of CNTs have been widely investigated by different groups and showed that their toxicity is related to composition, length, diameter and sizes.…”
Section: Discussionmentioning
confidence: 99%
“…MWNT has different toxicity such as inhalation toxicity, genotoxicity etc. [67][68][69] . Ag nanoparticle is one of the nanostructures used in different parts of life especially as the antimicrobial agent 33,34 .…”
Section: Journal Of Biomedical Materials Research: Part Amentioning
confidence: 99%
“…Apoptotic studies on RPE cells with G-OH were determined by caspase 3 activity assay as the activation cytosolic caspase-3 indicating the cell apoptosis [35,36]. As shown in Figure 2(a), the Capaspase-3 activity of ARPE-19 cells cultured with less than 50 μg/mL G-OH over 48 h didn't show much difference.…”
Section: Capspase 3 Activity and Western Blotsmentioning
confidence: 99%
“…45 The agglomeration of functionalized MWCNTs was previously discovered around human ocular cells without significant changes in their morphology. 46 As observed in Figure 5C and D, internalized MWCNT-FITC conjugates were colocalized with blue-colored shapes of endothelial cells, with Pearson's coefficient of 0.915 indicating nanotube uptake without apparent adverse effects on cell viability.…”
Section: Resultsmentioning
confidence: 67%